2018
DOI: 10.1111/dgd.12578
|View full text |Cite
|
Sign up to set email alerts
|

Plant adaptation and speciation studied by population genomic approaches

Abstract: Ever since Darwin, one of the major challenges in evolutionary biology is to unravel the process and mechanisms of adaptation and speciation. Population genomics—the analysis of whole‐genome polymorphism data from large population samples—is a critical approach to study adaptation and speciation, as population genomics datasets enable us to: (1) perform genome‐wide association studies (GWAS) to find genes underlying adaptive phenotypic variations; (2) scan the footprints of selection across the genome to pinpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 105 publications
0
18
0
Order By: Relevance
“…Recently, using natural populations and natural accessions of model species for molecular biology and genetics, such as Arabidopsis thaliana , researchers have applied advanced techniques to dissect adaptation genetically (Savolainen et al 2013; Weigel and Nordborg 2015). Genome-wide association studies (GWAS) have identified the genes involved in adaptation to biotic and abiotic environments in A. thaliana (reviewed in Bamba et al 2019). For example, genome-wide single-nucleotide polymorphisms (SNPs) have been investigated for associations with the environmental conditions of the source sites (Hancock et al 2011) and with fitness measures in a common garden experiment (Fournier-Level et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using natural populations and natural accessions of model species for molecular biology and genetics, such as Arabidopsis thaliana , researchers have applied advanced techniques to dissect adaptation genetically (Savolainen et al 2013; Weigel and Nordborg 2015). Genome-wide association studies (GWAS) have identified the genes involved in adaptation to biotic and abiotic environments in A. thaliana (reviewed in Bamba et al 2019). For example, genome-wide single-nucleotide polymorphisms (SNPs) have been investigated for associations with the environmental conditions of the source sites (Hancock et al 2011) and with fitness measures in a common garden experiment (Fournier-Level et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of a species to adapt depends on their phenotypic plasticity and potential for genetic adaptation, with the latter being conditioned on the species diversity and the rate of incoming beneficial alleles. A combination of genome‐wide scans and field experiments has previously detected local climate adaptation, defined as higher fitness in a native population, in multiple systems, with complex or polygenic traits mainly underlying such adaptations (reviewed by Bamba, Kawaguchi, & Tsuchimatsu, 2019). In general, slow geological change and gradual selection pressures allow for the evolution of traits with a large number of small fitness effect variants.…”
Section: Figurementioning
confidence: 99%
“…Genetic variations can therefore modulate the local effects of environmental change (Parmesan 2006). Local adaptation can be constrained by variation in natural selection and gene ow (Kawecki and Ebert 2004, Leimu and Fischer 2008, Bamba et al 2018. Studies have revealed that local adaptation among provenances and populations of E.camaldulensis has been suggested from variation in adaptive phenotypes which correspond to local environment including: morphological traits (growth form, leaf thickness, stomatal density and phenology) (James and Bell 1995); growth rate (Otegbeye 1985); wood properties (El-Lakany 1980); physiological responses (Morshet 1981) and drought tollerance (Lemcoff et al 2002).…”
Section: Adaptive Species Strategiesmentioning
confidence: 99%